2008
DOI: 10.1152/japplphysiol.90400.2008
|View full text |Cite
|
Sign up to set email alerts
|

Time course of regression of the protection conferred by simulated high altitude to rat myocardium: correlation with mtNOS

Abstract: During acclimatization to sustained hypobaric hypoxia, retardation of age-associated decline in left ventricle mechanical activity and improved posthypoxic recovery were accompanied by upregulation of mitochondrial nitric oxide synthase (mtNOS). To evaluate the time course of regression of these effects on deacclimatization, rats exposed to 53.8 kPa in a hypopressure chamber for 5 mo were returned to 101.3 kPa, whereas controls remained at 101.3 kPa throughout the study. At three time points, contractile funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
23
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 50 publications
5
23
0
Order By: Relevance
“…It has been shown previously that heart mitochondria exhibit immunoreactivity with anti-iNOS antibodies (15,19,47). By means of a similar approach to the one of this study, La Padula et al (27) recently reported a decrease in heart mtNOS expression during the regression of the cardioprotection conferred by hypoxia, using not only anti-nNOS but also anti-iNOS in Western blot experiments. The 51-57% homology reported for nNOS, iNOS, and eNOS, and the cross-reactivity of isoform-specific anti-NOS antibodies could contribute to explain the conflicting results (24,26).…”
Section: Discussionsupporting
confidence: 64%
“…It has been shown previously that heart mitochondria exhibit immunoreactivity with anti-iNOS antibodies (15,19,47). By means of a similar approach to the one of this study, La Padula et al (27) recently reported a decrease in heart mtNOS expression during the regression of the cardioprotection conferred by hypoxia, using not only anti-nNOS but also anti-iNOS in Western blot experiments. The 51-57% homology reported for nNOS, iNOS, and eNOS, and the cross-reactivity of isoform-specific anti-NOS antibodies could contribute to explain the conflicting results (24,26).…”
Section: Discussionsupporting
confidence: 64%
“…This upregulation was associated with a preservation of the papillary muscle contractile parameters upon aging and improved tolerance to postischemic contractile dysfunction. Using a similar approach, a decrease in heart mtNOS activity and expression during the regression of the cardioprotection conferred by hypoxia has been reported (79). Other studies showed that liver mtNOS activity is upregulated after acute exposure to hypoxia (80,118).…”
Section: Role Of No In the Regulation Of Heart Functionmentioning
confidence: 79%
“…In the heart, however, the most convincing data implicate nNOS as the primary candidate for the cytoplasmic NOS izosyme targeted into mitochondria (40,72,142). Evidence in favor of eNOS (10,66,140) and iNOS (45,60,79,129) (Fig. 2B) presence in heart mitochondria has also been published.…”
Section: Heart Nossmentioning
confidence: 95%
See 2 more Smart Citations